Effect of fusion and arthroplasty for cervical degenerative disc disease in patients with physically demanding occupations - Harjot Uppal, MBA; George Abdelmalek, MD; Neil Patel, MD; Daniel Coban, MD; Stuart Changoor, MD; Nikhil Sahai, MD; Kumar Sinha, MD; Ki Hwang, MD; Arash Emami, MD (North American Spine Society Journal)
ABSTRACT: Background: Cervical degenerative disc disease (DDD) significantly affects the quality of life in labor-intensive careers. When conservative measures fail, either anterior cervical discectomy and fusion (ACDF) or cervical disc arthroplasty (CDA) may be indicated. Although ACDF is the gold standard, it can limit motion, whereas CDA preserves motion and may reduce adjacent segment disease (ASD). Few studies compare these surgeries in physically demanding populations, and the influence of workers’ compensation (WC) on outcomes is unclear. Therefore, the purpose of this study is to compare the outcomes of CDA versus ACDF in patients with labor-intensive jobs and to assess how workers' compensation (WC) status influences these outcomes. Methods: In this prospective cohort study, 300 (CDA: 150, ACDF: 150) patients with 1- or 2-level cervical DDD with labor-intensive jobs were enrolled, including a subgroup of 60 WC patients (CDA: 30, ACDF: 30). Participants were followed for a minimum of 2 years. Data collected included demographic details, perioperative events, and complication rates. Functional outcomes were measured using the Visual Analog Scale for neck and arm pain (VAS-neck, VAS-arm) and the Neck Disability Index (NDI), with attention to timelines for returning to full-time work. Results: CDA patients returned to full-time work faster (4.3 vs 6.7 months, p=.025). More CDA patients resumed work by 6 weeks (p=.018) and 3 months (p=.022), though these differences waned by 6 months. WC patients had slower returns overall (CDA WC: 7.5 vs 5.0 weeks for non-WC, p=.015). CDA showed greater NDI improvement at all time points and significantly lower ASD incidence (1.3% vs. 26.7%, p<.001). Complications were comparable. Conclusion: CDA may facilitate faster work return, better recovery, and lower ASD risk in labor-intensive patients. WC status correlates with delayed recovery, suggesting a need for tailored approaches. Further research is necessary to confirm these findings and refine patient selection.